Blue skies - Carr, Robyn (Don Mills, Ont. : Harlequin, 2004)
Nikki Burgess, Dixie McPherson, and Carlisle Bartlett-- three people who have been hurt by past relationships-- take a chance on changing their lives by joining a team that intends to start a new airline in Las Vegas.
Keywords: Man-woman relationships -- Fiction; Female friendship -- Fiction; Airlines -- Employees -- Fiction; Las Vegas (Nev.) -- Fiction; Love stories